VD_FINDINFO Décision / 2015 / 366 vom 29. April 2015 - VD Tribunal cantonal (2015)
ADMISSION DE LA DEMANDE, ACTE D'ORDRE SEXUEL AVEC UN ENFANT, VOIES DE FAIT, NON-LIEU | 126 al. 2 CP, 187 ch. 1 CP, 319 CPP (CH)